A catalyst for directly converting synthesis gas into gasoline with low aromatic content and its application

By using a composite catalyst, combined with metal oxides and metal-modified MFI structure molecular sieve, the problem of high aromatic selectivity in the process of direct conversion of synthesis gasoline preparation is solved, and the catalytic effect of low aromatic content, high CO conversion and low by-products is achieved.

CN116173935BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111433490.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-29
Publication Date
2025-04-11
Estimated Expiration
2041-11-29

AI Technical Summary

Technical Problem

In the prior art, during the direct conversion of synthesis gasoline, the aromatic hydrocarbons of the product are highly selective, resulting in insufficient combustion, carbon deposits and toxic gases, which violates the national gasoline standards.

Method used

A composite catalyst is used, which consists of metal oxide and metal-modified MFI structural molecular sieve, and is combined by mechanical mixing or bedding filling to ensure the appropriate proportion and distribution of modified metal elements in the catalyst.

Benefits of technology

The aromatic content in gasoline is significantly reduced, the CO conversion rate and gasoline selectivity are improved, and the selectivity of by-product methane is less than 15%, meeting the requirements of national gasoline standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a catalyst for catalyzing the direct conversion of synthesis gas to produce low aromatic content gasoline and its application, belonging to the technical field of preparing gasoline from synthesis gas. The catalyst is a composite catalyst, including component I and component II, wherein component I is a metal oxide, component II is a metal-modified MFI structure molecular sieve, and component I and component II are mechanically mixed or layered in a fixed bed or a moving bed. The composite catalyst of the present invention performs a synthesis gas conversion reaction in a fixed bed or a moving bed, and the reaction process has a high product yield and selectivity, and the product is prepared from C5-C 11 Liquid fuel selectivity can reach 50-80%, C5-C 11 The selectivity of aromatics is less than 35%, and the selectivity of by-product methane is less than 15%, which has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparing gasoline from synthesis gas, and particularly relates to a catalyst for catalyzing direct conversion of synthesis gas to prepare gasoline with low aromatic content and application thereof. Background Art

[0002] With the development of economy and the improvement of living standard, the demand of liquid fuel and chemicals is also rising sharply year by year. At present, gasoline production is mainly obtained by catalytic reforming of heavy naphtha.

[0003] my country is rich in coal resources. The technical route of using coal as raw material, gasifying to obtain synthesis gas (i.e., a mixture of CO and H2), converting synthesis gas into methanol, and then converting methanol into gasoline through dimethyl ether has matured and entered industrialization. This route provides an important new route for the production of liquid fuels from carbon resources such as coal and natural gas. However, if the direct conversion of synthesis gas can be achieved without the direct route of methanol synthesis and methanol dehydration to dimethyl ether, it can not only simplify the process flow, but also reduce unit operations, investment and energy consumption. The traditional Fischer-Tropsch pathway can realize the direct conversion of synthesis gas to prepare liquid fuels. However, due to the limitations of its reaction mechanism, CO and H2 molecules undergo dissociative adsorption on the catalyst surface to generate surface C atoms and O atoms. C atoms and O atoms react with hydrogen adsorbed on the catalyst surface to form methylene (CH2) intermediates and release water molecules at the same time. The methylene intermediates undergo free polymerization on the catalyst surface through migration insertion reactions to generate hydrocarbon products containing different numbers of carbon atoms (from one to thirty, sometimes even hundreds of carbon atoms). The carbon atom number distribution of the hydrocarbon products of the entire reaction is wide, and the selectivity of the target product is low, such as the selectivity of gasoline is less than 50%. The use of oxides + molecular sieves to form a bifunctional catalyst can separate CO activation and CC coupling on two active centers, thereby breaking the limitation of product selectivity in the traditional Fischer-Tropsch process, and gasoline can be obtained in one step. Compared with other molecular sieves, ZSM-5 molecular sieves show higher space-time yield and better stability in the process of synthesizing gasoline from syngas. However, in the process of synthesizing gasoline from syngas, ZSM-5 molecular sieves have a high selectivity for aromatics from gasoline products. Aromatics are prone to incomplete combustion in the combustion chamber of the engine, which not only causes carbon deposits in the engine, but also produces toxic and harmful gases such as CO. Therefore, gasoline standards in various countries have strict regulations on the content of aromatics. my country's National VI gasoline standard stipulates that the aromatic content in gasoline is not more than 35%. Therefore, it is of great significance to develop a catalyst and method for directly converting syngas into gasoline with low aromatic content in one step. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to provide a catalyst for catalyzing the direct conversion of synthesis gas into gasoline with low aromatic content and its application.

[0005] The object of the present invention is to achieve the following:

[0006] A catalyst, characterized in that: the catalyst is a composite catalyst, comprising component I and component II, wherein the active ingredient of component I is a metal oxide, and component II is a metal-modified MFI structure molecular sieve.

[0007] Based on the above technical solution, the mixing method of component I and component II is mechanical mixing, or bed layer filling, and component II is placed downstream of component I according to the flow direction of the raw materials.

[0008] Based on the above technical solution, the metal oxide of component I is MnO y 、MnCr x O y 、MnAl x O y 、MnZr x O y 、MnIn x O y 、ZnMn x O y 、ZnCr x O y 、ZnAl x O y 、ZnCr x Al z O y 、ZnGa x O y 、ZnO、CeO2、ZnGa x Al z O y 、 In2O3、 ZnIn x O y 、CeZr x O y 、CoAl x O y 、FeAl x O y One or more of the following: the value range of x is 0.01 to 100, the value range of z is 0.01-100, and the value range of y is 0.001-1000.

[0009] Based on the above technical solution, the MnO y , ZnO, CeO2, In2O3 have a specific surface area of ​​1-100m 2 / g.

[0010] Based on the above scheme, preferably, the MnCr x O y 、MnAlx O y 、MnZr x O y 、MnIn x O y 、ZnMn x O y 、ZnCr x O y 、ZnAl x O y 、ZnCr x Al z O y 、ZnGa x O y 、ZnGa x Al z O y 、ZnIn x O y 、CeZr x O y 、CoAl x O y 、FeAl x O y The specific surface area is 5-300m 2 / g.

[0011] Based on the above technical solution, in the metal-modified MFI structured molecular sieve, the type of modified metal is one or more of Zn, Ga, Ni, Fe, Cu, Mn, Cr, Co, and In.

[0012] Based on the above scheme, the metal modification method includes one or more of an impregnation method, an ion exchange method, a hydrothermal method, and a solid phase ion exchange method.

[0013] Based on the above scheme, the specific process of the impregnation method is: dissolving the metal salt in water or an organic solvent, adding the MFI structure molecular sieve, stirring at room temperature for 2-10 hours, drying, and calcining at 300-600°C.

[0014] Based on the above scheme, the specific process of the ion exchange method is: dissolve the metal salt in water or an organic solvent, add MFI structure molecular sieve, stir for 2-3 hours at 50-90°C, filter, repeat the above process once or twice, and after drying the obtained product, calcine at 300-600°C.

[0015] Based on the above scheme, the specific process of the hydrothermal method is: according to a certain proportion, the silicon source, aluminum source, template agent, metal salt and water are added to the hydrothermal reactor respectively and stirred for 2-10 hours, hydroheated at 150-190℃ for 24-720 hours, and the obtained sample is centrifuged, washed, dried, and calcined at 300-600℃.

[0016] Based on the above scheme, the specific process of the solid phase ion exchange method is: in a glove box, the metal salt and the MFI structure molecular sieve are respectively ground and mixed evenly, and then calcined at 300-600°C.

[0017] Based on the above technical solution, the proportion of the modified metal element in component II is 0.005-15wt%; preferably, the proportion of the modified metal element in component II is 0.01-10wt%;

[0018] Based on the above technical scheme, the molecular sieve framework element composition of the MFI topological structure of component II is one or more of Si-O, Si-Al-O, Si-BO, Si-Al-Ti-O, Ga-Si-Al-O, Mg-Al-PO, and As-Si-O; the molecular sieve has medium-strong acid characteristics, and the amount of medium-strong acid sites is 0.005-2.5 mol / kg; preferably 0.01-1 mol / kg; wherein the temperature range corresponding to the peak top of the NH3-TPD desorption peak corresponding to the medium-strong acid is 200-500°C; acetone is used as a probe molecule, 13 The C-NMR chemical shifts were in the range of 210-220 ppm.

[0019] The acid strength is defined by the NH3-TPD peak, including three types of acidity: weak acid, medium acid, and strong acid;

[0020] The NH3-TPD is based on the desorption peak position of NH3. The position of the desorption peak refers to the thermal conductivity signal of desorbed NH3 recorded by TCD under standard test conditions, under the test conditions of the ratio of sample mass w to carrier gas flow rate f (w / f) = 100g·h / L and a heating rate of 10°C / min, and a desorption curve is drawn. The inorganic solid is divided into three acid strengths according to the apex of the curve peak position; weak acid refers to the acidic position with NH3 desorption temperature less than 275°C; medium-strong acid refers to the acidic position with NH3 desorption temperature between 275-500°C; strong acid refers to the acidic position with NH3 desorption temperature greater than 500°C.

[0021] Based on the above technical solution, in the composite catalyst, the weight ratio of the active ingredient in component I to component II is 0.1-20:1, preferably 0.3-5:1.

[0022] Based on the above technical scheme, a dispersant is further added to the component I, and the metal oxide is dispersed in the dispersant; the dispersant is one or more of Al2O3, SiO2, Cr2O3, ZrO2, TiO2, Ga2O3, activated carbon, graphene, and carbon nanotubes; in the component I, the content of the dispersant is 0.05-90wt%, and the rest is metal oxide.

[0023] Another aspect of the present invention provides a method for directly converting synthesis gas into gasoline, which uses synthesis gas as a reaction raw material, performs a conversion reaction on a fixed bed or a moving bed, and uses the above-mentioned catalyst as the catalyst;

[0024] The synthesis gas is a H2 / CO mixed gas, the H2 / CO ratio is 0.2-3.5, preferably 0.3-2.5; the synthesis gas pressure is 0.5-10MPa, preferably 1-8MPa; the reaction temperature is 300-600°C, preferably 350-500°C; the space velocity is 300-15000 ml / g cat / h, preferably 500-12000ml / g cat / h, more preferably 1000-10000ml / g cat / h.

[0025] Beneficial Effects

[0026] 1. The method of directly converting synthesis gas to produce low aromatics content gasoline of the present invention is different from the traditional Fischer-Tropsch synthesis method for producing liquid fuels. It realizes the efficient conversion of synthesis gas into liquid fuel directly in one step, and the selectivity of by-product methane is less than 15%.

[0027] 2. Compared with the composite catalyst of component II using the MFI structure molecular sieve without metal modification, the metal-modified MFI structure molecular sieve of the present invention as the composite catalyst of component II catalyzes the conversion of synthesis gas into gasoline, and the content of aromatics in the product is significantly reduced, and the CO conversion rate and gasoline selectivity are significantly improved, which has significant economic value. DETAILED DESCRIPTION

[0028] The present invention is further described below by way of examples, but the scope of the claims of the present invention is not limited by these examples. Meanwhile, the examples only provide partial conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose.

[0029] The specific surface area of ​​the sample can be tested by nitrogen or argon physical adsorption method.

[0030] Example 1 Preparation of Catalyst Component I

[0031] Preparation of catalyst component ZnCr by coprecipitation method x Al z O y: Zinc nitrate, aluminum nitrate and chromium nitrate are used as precursors (Zn / Cr / Al=1 / 1 / 2, Zn is 50mM), and mixed with ammonium carbonate in water at room temperature (ammonium carbonate is used as a precipitant, and ammonium carbonate is excessive or the molar ratio of ammonium ions to metal ions is 1:1); the mixed solution is aged at 90°C for 20 hours, then taken out, washed, filtered and dried, and the obtained solid is calcined at 500°C in an air atmosphere to obtain ZnCrAl metal oxide, recorded as OX-1.

[0032] The specific surface area of ​​the obtained ZnCrAl metal oxide is 115m 2 / g.

[0033] The catalyst component ZnAl was prepared by coprecipitation method. x O y : Zinc nitrate and aluminum nitrate are used as precursors (Zn / Al=1 / 2, Zn is 50mM), and mixed with ammonium bicarbonate in water at room temperature (ammonium bicarbonate is used as a precipitant, and ammonium carbonate is excessive or the molar ratio of ammonium ions to metal ions is 2:1); the mixed solution is aged at 90°C for 5 hours, then taken out, washed, filtered and dried, and the obtained solid is calcined at 500°C in an air atmosphere to obtain ZnAl metal oxide, recorded as OX-2.

[0034] The specific surface area of ​​the obtained ZnAl metal oxide is 150m 2 / g.

[0035] Preparation of ZnMn containing ZrO2 dispersant by coprecipitation method x O y :Zinc nitrate and manganese nitrate are used as precursors (Zn / Mn=1 / 1, Zn is 50mM) and dissolved in water, ZrO2 dispersant (ZrO2 content is 50%) is added, and ammonium carbonate precipitant (ammonium carbonate is used as precipitant, ammonium carbonate is excessive or the molar ratio of ammonium ion to metal ion is 2.5:1) is added; the mixed solution is aged at 70°C for 3 hours, then taken out for washing, filtering and drying, and the obtained solid is calcined at 500°C in air atmosphere to obtain ZnMn containing ZrO2 dispersant. x O y Oxide, recorded as OX-3.

[0036] After testing, the specific surface area of ​​the obtained metal oxide is 78m 2 / g.

[0037] Preparation of catalyst component ZnCr by coprecipitation method x O y: Zinc nitrate and chromium nitrate are used as precursors (Zn / Cr=1 / 1, Zn is 50mM), and mixed with ammonium bicarbonate in water at room temperature (ammonium bicarbonate is used as a precipitant, and ammonium carbonate is excessive or the molar ratio of ammonium ion to metal ion is 2:1); the mixed solution is aged at 90°C for 5 hours, then taken out for washing, filtering and drying, and the obtained solid is calcined at 500°C in an air atmosphere to obtain ZnCr metal oxide, which is recorded as OX-4.

[0038] The specific surface area of ​​the obtained ZnCr metal oxide is 90m 2 / g.

[0039] The catalyst component MnCr was prepared by coprecipitation method. x O y : Zinc nitrate and chromium nitrate are used as precursors (Mn / Cr=2 / 1, Mn is 50mM), and are mixed with ammonium bicarbonate in water at room temperature (ammonium bicarbonate is used as a precipitant, and ammonium carbonate is excessive or the molar ratio of ammonium ions to metal ions is 2:1); the mixed solution is aged at 90°C for 5 hours, then taken out for washing, filtering and drying, and the obtained solid is calcined at 500°C in an air atmosphere to obtain MnCr metal oxide, which is recorded as OX-5.

[0040] The specific surface area of ​​the obtained MnCr metal oxide is 130m 2 / g.

[0041] Example 2 Preparation of Catalyst Component II

[0042] The medium-strong acid described in the present invention can be tested by solid nuclear magnetic H spectrum, NH3-TPD, infrared, chemical titration, etc. However, the acidity test method is not limited to the above test methods.

[0043] The MFI structure molecular sieve in component II of the present invention can be a purchased commercial product (select the molecular sieve that meets the claims) or a self-prepared molecular sieve.

[0044] Component II was prepared by impregnation method, taking commercial ZSM-5 (purchased from Nankai Catalyst Factory) as an example:

[0045] (a) Take a certain amount of zinc nitrate and dissolve it in 10 ml H2O, add 5 g ZSM-5 molecular sieve, stir at room temperature for 10 hours, dry, and calcine at 500℃ for 2 hours to obtain Zn-modified ZSM-5; the Zn element content is 1%. It is recorded as ZEO-1.

[0046] (b) Using a similar method, the precursors of Ga, Ni, Fe, Cu, Mn, Cr, Co, In, etc. were dissolved in water, 5 g of ZSM-5 molecular sieve was added, stirred at room temperature for 10 h, dried, and calcined at 500 ° C for 2 h to obtain Ga, Ni, Fe, Cu, Mn, Cr, Co, In modified ZSM-5; the metal content is shown in Table 1. They are respectively recorded as ZEO-2, ZEO-3, ZEO-4, ZEO-5, ZEO-6, ZEO-7, ZEO-8, and ZEO-9.

[0047] Component II was prepared by ion exchange method, taking commercial ZSM-5 (purchased from Nankai Catalyst Factory) as an example:

[0048] A certain amount of precursors of Zn, Ga, Ni, Fe, Cu, Mn, Cr, Co, In, etc. were dissolved in water to obtain a 1 mol / L aqueous solution, a certain amount of ZSM-5 molecular sieve was added, the mixture was stirred for 2-3 hours in a water bath at 80°C, and filtered. The above process was repeated several times to obtain a modified ZSM-5 molecular sieve with the required metal content. The final product was dried and calcined at 500°C.

[0049] Component II was prepared by hydrothermal method:

[0050] Silica sol, tetrapropylammonium hydroxide, aluminum nitrate and water were added to the reactor in a molar ratio of SiO2:tetrapropylammonium hydroxide:Al2O3:H2O = 1:0.06:0.01:240, and a certain amount of precursors of Zn, Ga, Ni, Fe, Cu, Mn, Cr, Co, In, etc. were added respectively. The samples were stirred at room temperature for 3 h, hydroheated at 170 ° C for 24-120 h, centrifuged, washed and dried, and finally calcined at 500 ° C for 3 h.

[0051] Component II was prepared by solid phase ion exchange method, taking commercial ZSM-5 (purchased from Nankai Catalyst Factory) as an example:

[0052] In a glove box, precursors of Zn, Ga, Ni, Fe, Cu, Mn, Cr, Co, In, etc. were ground and mixed evenly with ZSM-5 molecular sieve, and calcined in a muffle furnace at 500°C for 2h.

[0053] Table 1. Type, content and preparation method of modified metal elements in component II

[0054] Component II Metal element type Metal element content (%) Preparation method ZEO-1 Zn 0.01 Dipping method ZEO-2 Ga 0.05 Dipping method ZEO-3 Ni 0.1 Dipping method ZEO-4 Fe 0.5 Dipping method ZEO-5 Cu 0.03 Dipping method ZEO-6 Mn 10 Dipping method ZEO-7 Cr 5 Dipping method ZEO-8 Co 3 Dipping method ZEO-9 In 1 Dipping method ZEO-10 Zn 0.03 Ion exchange method ZEO-11 Ga 1 Ion exchange method ZEO-12 Ni 0.25 Ion exchange method ZEO-13 Cu 0.2 Ion exchange method ZEO-14 Fe 0.3 Ion exchange method ZEO-15 Cu 0.001 Hydrothermal method ZEO-16 Fe 0.3 Hydrothermal method ZEO-17 Ga 0.6 Hydrothermal method ZEO-18 Ni 0.09 Hydrothermal method ZEO-19 Zn 1.3 Hydrothermal method ZEO-20 Ga 1.2 Solid phase ion exchange ZEO-21 Zn 3.3 Solid phase ion exchange ZEO-22 Fe 0.6 Solid phase ion exchange ZEO-23 Cu 1.1 Solid phase ion exchange ZEO-24 Co 0.04 Solid phase ion exchange

[0055] Comparative Example

[0056] Preparation of unmodified ZSM-5 molecular sieve:

[0057] Among them, commercial ZSM-5 (purchased from Nankai Catalyst Factory, SiO2 / Al2O3=100) is denoted as ZEO-25.

[0058] Commercial molecular sieve prepared by hydrothermal synthesis (SiO2 / Al2O3=110): silica sol, tetrapropylammonium hydroxide, aluminum nitrate and water were added to the reactor at a molar ratio of SiO2:tetrapropylammonium hydroxide:Al2O3:H2O=1:0.06:0.09:240, stirred at room temperature for 3h, hydrothermal at 170℃ for 24-120h, centrifuged, washed and dried, and finally calcined at 500℃ for 3h. It is denoted as ZEO-26.

[0059] Preparation of modified TON structure molecular sieve (ZSM-22): Using the impregnation method, 5g of ZSM-22 molecular sieve (purchased from Nankai Catalyst Factory) was added to a certain amount of manganese nitrate solution, impregnated at room temperature, dried at 110 degrees, and calcined at 500 degrees for 3h, recorded as ZEO-27, in which the Mn content was 5%.

[0060] Example 3 Preparation of Catalyst

[0061] Preparation of composite catalyst:

[0062] (1) Mechanical mixing: The compounding can be carried out by one or more of mechanical stirring, ball milling, shaking mixing, and mechanical grinding, as follows:

[0063] Mechanical stirring: In a stirring tank, use a stirring rod to mix component I and component II. By controlling the stirring time (5min-120min) and speed (30-300 rpm), the mixing degree and relative distance between component I and component II can be adjusted.

[0064] Ball milling: The abrasive and catalyst are rolled at high speed in the grinding tank to produce strong impact and crushing on the catalyst, so as to disperse and mix components I and II. The particle size and relative distance of the catalyst can be adjusted by controlling the ratio of the abrasive (the material can be stainless steel, agate, quartz. Size range: 5mm-15mm) and the catalyst (mass ratio range: 20-100:1).

[0065] Shaking table mixing method: pre-mix component I and component II and put them into a container; mix component I and component II by controlling the reciprocating oscillation or circular oscillation of the shaker; achieve uniform mixing and adjust their relative distance by adjusting the oscillation speed (range: 1-70 rpm) and time (range: 5min-120min).

[0066] Mechanical grinding method: pre-mix component I and component II and put them into a container; under a certain pressure (range: 5 kg-20 kg), the grinding tool and the mixed catalyst are moved relative to each other (speed range: 30-300 rpm) to adjust the catalyst particle size, relative distance and achieve uniform mixing.

[0067] (2) Layered loading: Components I and II are loaded in layers according to a certain ratio. According to the flow direction of the raw materials, component II is placed downstream of component I.

[0068] The above methods were used to prepare the composite catalysts. The specific preparation of the composite catalysts and their parameter characteristics are shown in Table 2.

[0069] Table 2. Preparation of composite catalysts and their parameter characteristics

[0070]

[0071]

[0072] Example 4 Application of Catalyst

[0073] The composite catalyst prepared as above is loaded into a fixed bed reaction device, which is equipped with a gas mass flowmeter and an online product analysis chromatograph (the tail gas of the reactor is directly connected to the quantitative valve of the chromatograph for periodic real-time sampling and analysis); the synthesis gas is a H2 / CO mixed gas, and the H2 / CO ratio, reaction temperature, reaction pressure, space velocity and other parameters of the catalyst of the present invention and the comparative catalyst in the fixed bed are shown in Table 3.

[0074] Table 3. Specific application of catalysts and their effect data

[0075]

[0076] As can be seen from the table above, the catalyst component II used in the comparative composite catalyst Cat25-26 is a non-metal-modified MFI molecular sieve, and the CO conversion rate and gasoline selectivity are significantly lower, while the aromatic content in the gasoline product is significantly higher than the experimental results of the composite catalyst of the metal-modified MFI molecular sieve. Cat27 uses a metal-modified ZSM-22 molecular sieve instead of an MFI molecular sieve, and its byproduct methane CH4 selectivity is significantly higher, and the CO conversion rate is significantly lower. It can be seen from the table above that only when component II is selected as a metal-modified MFI molecular sieve can high gasoline selectivity, low aromatic selectivity and low methane selectivity be achieved in the process of catalytic synthesis gas conversion into gasoline.

Claims

1. A catalyst, characterized in that: The catalyst is a composite catalyst, comprising component I and component II, wherein the active component of component I is a metal oxide, and component II is a metal-modified ZSM-5 molecular sieve; The mixing method of the components I and II is mechanical mixing or filling in separate beds, and according to the flow direction of the raw materials, the component II is placed downstream of the component I; The metal oxide in component I is MnCr x O y 、ZnMn x O y 、ZnCr x O y 、ZnAl x O y 、ZnCr x Al z O y One or more of the above; the value range of x is 0.01-100, the value range of z is 0.01-100, and the value range of y is 0.001-1000; In the metal-modified ZSM-5 molecular sieve of component II, the type of modified metal is one or more of Zn, Ga, Ni, Fe, Cu, Mn, Cr, Co, and In; the method of metal modification includes one or more of impregnation method, ion exchange method, hydrothermal method, and solid phase ion exchange method; The proportion of the modified metal element in component II is 0.005-15; The molecular sieve has medium-strong acid characteristics, and the amount of medium-strong acid sites is 0.005-2.5 mol / kg.

2. The catalyst according to claim 1, characterized in that: The MnCr x O y 、ZnMn x O y 、ZnCr x O y 、ZnAl x O y 、ZnCr x Al z O y The specific surface area is 5-300 m 2 / g.

3. The catalyst according to claim 1, characterized in that: The proportion of the modified metal element in component II is 0.01-10 wt%.

4. The catalyst according to claim 1, characterized in that: The amount of medium-strong acid sites in the molecular sieve is 0.01-1 mol / kg.

5. The catalyst according to claim 1, characterized in that: The weight ratio of the active ingredient in component I to component II is 0.1-20:

1.

6. The catalyst according to claim 1, characterized in that: The component I is further added with a dispersant, in which the metal oxide is dispersed; the dispersant is Al2O3, SiO2, Cr2O 3、 One or more of ZrO2, TiO2, Ga2O3, activated carbon, graphene, and carbon nanotubes; in the component I, the content of the dispersant is 0.05-90 wt%, and the rest is metal oxide.

7. A method for directly converting synthesis gas into gasoline, characterized in that: Using synthesis gas as a reaction raw material, a conversion reaction is carried out on a fixed bed or a moving bed, and the catalyst used is the catalyst described in any one of claims 1 to 6; The synthesis gas is a H2 / CO mixed gas with a H2 / CO ratio of 0.2-3.5; the pressure of the synthesis gas is 0.5-10 MPa; the reaction temperature is 300-600 °C; the space velocity is 300-15000 ml / g cat / h.

8. The method according to claim 7, characterized in that: The ratio of H2 / CO is 0.3-2.5; the pressure of the synthesis gas is 1-8 MPa; the reaction temperature is 350-500 °C; the space velocity is 500-12000 ml / g cat / h.

9. The method according to claim 7, characterized in that: The method uses synthesis gas as a reaction raw material to directly convert it into gasoline in one step, wherein the selectivity of gasoline reaches 50-80%, C5-C 11 The selectivity of aromatics is less than 35%, while the selectivity of by-product methane is less than 15%.